Transformation of library and information management: Decolonization or Indigenization?. (October 2021) - Lilley, Spencer
This article considers how colonization has impacted on Indigenous knowledge systems. It discusses the issues that need to be addressed by institutions, library and information professionals, and professional associations to ensure that they are able to meet the needs of the Indigenous people in their communities. The article addresses why this transformation is required and outlines the issues that will need to be changed through a decolonization or indigenization process.